Prevalence of Anaemia in Kerala State, Southern India - A Systematic Review - Rakesh, PuruShothama Suseela (J Clin Diagn Res, 2017)
INTRODUCTION: Anaemia is the most common nutritional problem affecting children, adolescents and women. A systematic review was undertaken to find out the prevalence of anaemia and to identify the trend in the prevalence of anaemia in Kerala state, Southern India. AIM: The aim of the review was to identify the prevalence of anaemia in Kerala and to comment on its trend across last 25 years. MATERIALS AND METHODS: PubMed and google scholar searches and scanning of reference lists were used to identify studies. All population based studies on anaemia from Kerala, irrespective of its designs, published between Jan 1(st) 1990 to Dec 31(st) 2015 were included. Data extraction and quality assessment were carried out using structured proformas. Due to the heterogeneity of reviewed studies, meta-analysis was not done. A narrative approach was used. RESULTS: A total of 10 studies in addition to two major survey reports- National Family Health Survey (NFHS) and District Level Household Survey (DLHS) were included in the final analysis. Prevalence of anaemia among adolescents from recent study reports was around 30% and prevalence of severe anaemia was less than 1% in all studies. Anaemia among tribal women and children were in the range of 78.3% to 96.5%. A key finding of this review was the paucity of data and inconsistency in haemoglobin estimation methods and population characteristics which made comparisons impossible. CONCLUSION: The current prevalence of anaemia in Kerala is unclear. Though, there are many studies and reports regarding prevalence of anaemia in the state, those results could not be combined due to non uniform haemoglobin estimation methods. Standardised prospective study of general population including subgroups will be necessary.